73.5k views
4 votes
Given that f(x) = x2 + 1 and g(x) = -3, multiply the functions (gºf)(x).

A) (gºf)(x) = -3x2 - 3
B)(gºf)(x) = -3x2 + 3
C)(gºf)(x) = 3x2 + 3
D)(g. f)(x) = 3x2 - 3

1 Answer

0 votes

Answer:


(g\cdot f) = -3x^2-3

Explanation:


f(x) = x^2 + 1


g(x) = -3

The problem state to multiply the function
f and
g so the symbol seems to be incorrect.

We actually want to calculate


g(x) f(x) =gf(x) = (-3) \cdot (x^2+1)= -3x^2-3

Note


g\circ f(x)=g(f(x))=g(x^2+1)=-3

User Ringil
by
5.0k points